Pendampingan Pencatatan Laporan Keuangan pada UMKM Pelayanan Jasa Laundry dengan Aplikasi Buku Kas - Nova Astriana Lestari; Zaenal Wafa (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
Micro, Small and Medium Enterprises (MSMEs) in laundry services, Lestari Laundry and Aisyah laundry which have deficiencies in bookkeeping and recording financial reports, so that they become adequate targets for implementing the recording of financial reports for MSMEs in laundry services in community service MSMEs in the surrounding area. This program aims to serve the community by referring to assistance in recording MSME financial reports based on the Cash Book application. The methods applied in implementing this community service include observation, interviews, literature study surveys, training and education, practical demonstrations, direct guidance, and use of cash books. By implementing assistance in recording financial reports, using a cash book application, it can help MSMEs understand how and utilize social media with a cash book application. Apart from that, the results obtained from this service will allow MSME players to know more about financial reports that are more regular and accurate.